Reformulation of Juvenile Justice Policy in Handling Sexual Offenses by Children Under Twelve - Nurpahsari; Hilmy, Masdar; Erawati, Desi (Jurnal Ilmu Hukum Tambun Bungai, 2025)
Abstract: Law No. 11 of 2012 concerning the juvenile penal system faces challenges in immoral crimes. Article 1 paragraph (3) of the SPPA Law states that children who have not reached the age of 12 cannot be submitted to formal legal proceedings, but returned to their parents or referred to social institutions. Children who have become perpetrators of immoral acts committed by children under the age of 12 (twelve) years are under the supervision of negligent parents, so the author argues that by returning the child perpetrator to his parents, he is worried that he will repeat his act. This research is written normatively from library materials such as books, literature, journals and websites for the research to be discussed. The data analysis in this study is qualitative, meaning that it is based on the relevance of the data to the problem, not the quantity of (quantitative) data. Based on the results of the study, a larger effort to address children's social problems in Indonesia is to develop an interdisciplinary network that includes social institutions or services, law enforcement officials, and other related organizations in an effort to protect children. ABH (Children Facing the Law) rehabilitation is intended for children who have not reached the age of 12 years, who have committed or are suspected of committing criminal acts, and are undergoing legal proceedings at the level of investigation, prosecutor's office, or police. ABH rehabilitation is expected to be able to carry out its role, fulfill children's rights, solve problems, develop self-actualization and potential, and create a social environment that supports ABH's success in reintegrating into society with excellent learning and playing conditions like children of their age.